Polycentric monarchies : how did early modern Spain and Portugal achieve and maintain a global hegemony? - Cardim, Pedro (Brighton ; Portland, Or. : Sussex Academic Press, 2012)
Having succeeded in establishing themselves in Europe, Asia, Africa and the Americas, in the early 16th century Spain and Portugal became the first imperial powers on a worldwide scale. Between 1580 and 1640, when these two entities were united, they achieved an almost global hegemony, constituting the largest political force in Europe and abroad. Although they lost their political primacy in the seventeenth century, both monarchies survived and were able to enjoy a relative success until the early 19th century. The aim of this collection is to answer the question how and why their cultural an.
Epilogue Polycentric Monarchies: Understanding the Grand Multinational Organizations of the Early Modern Period Alberto Marcos MartínThe Editors and Contributors; Index.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
eBooks on EBSCOhost
Keywords: Imperialism -- History -- 17th century; Imperialism -- History -- 16th century; Portugal -- History -- Spanish dynasty, 1580-1640.; Spain -- History -- House of Austria, 1516-1700.; Impérialisme -- Histoire -- 17e siècle.; Impérialisme -- Histoire -- 16e siècle.; Portugal -- Histoire -- 1580-1640 (Dynastie espagnole); Espagne -- Histoire -- 1516-1700 (Maison d'Autriche); SOCIAL SCIENCE -- Emigration & Immigration; Imperialism; Portugal; Spain; Imperialismus; Hegemonie; Spanien; Portugal; Imperialism -- History -- 16th century; Spain -- History -- House of Austria, 1516-1700.; Portugal -- History -- Spanish dynasty, 1580-1640.; Imperialism -- History -- 17th century; 1500-1700; History